Distribusi Difference dari S-Box Berbasis Fungsi Balikan Pada GF(28) - Lestari, Andriani Adi; Yulianingsih, Nunik (Jurnal Matematika, 2016)
Substitution-box (s-box) is a basic component of block cipher which performs a substitution. Two powerful cryptanalysis techniques applied to block ciphers are linear cryptanalysis and differential cryptanalysis. The resistance against differential cryptanalysis can be achieved by eliminating high-probability differential trails. We should choose an s-box where the maximum difference propagation probability is as small as possible to eliminating high-probability differential trails. Nyberg proposed a method to construct the s-box by using the inverse mapping on a finite field then implements affine transformations on . In this study, we generate 47.104 s-box according to Nyberg. The experimental results showed that s-boxes have the maximum difference propagation probability with the same frequency.
Keywords: block cipher; difference distribution table; finite field; substitution-box keyword